FRI0459 Hla-b27 positive versus hla-b27 negative spondyloarthritis: different phenotypes but similar disease burden. (23rd January 2014) - Paramarta, J.; Van de Schoot, M.; Turina, M.; Ambarus, C.; Bijlsma, J.; De Rycke, L.; Baeten, D.
Abstract : Background: HLA-B27 has become increasingly important in the classification of both axial and peripheral spondyloarthritis (SpA) as this genetic factor is a major criterium in the new Assessment in SpondyloArthritis international Society (ASAS) criteria. How this may skew patient characteristics of axial and peripheral SpA remains unknown. Objectives: This study aimed to identify differences in clinical characteristics and disease activity between HLA-B27 positive and HLA-B27 negative SpA patients classified according to the ASAS criteria. Methods: 389 patients presenting on two dedicated SpA outpatient clinics and fulfilling the European Spondyloarthropathy Study Group (ESSG) criteria were included in a prospective observational cohort. Baseline characteristics were collected and patient's and physician's global assessment of disease activity, Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Ankylosing Spondylitis Disease Activity Score (ASDAS), 68 swollen and tender joint count, Schober, ESR and CRP were measured every 3 months. Data were analyzed with Mann Whitney U and chi square tests. Results: In the total SpA population, HLA-B27 positive patients (n=190) had a younger age at disease onset (median 30.9 vs. 38.8 years), more frequently inflammatory back pain (IBP) (89.5 vs. 73.1%) and sacroiliitis on X-ray (60.3 vs. 27.4%), less peripheral disease manifestations (arthritis 41.6 vs. 62.3%, enthesitis 32.1 vs. 47.9%), and more frequently uveitis (30.5 vs. 7.8%) and a positive family history (43.2 vs. 28.1%) than HLA-B27 negative SpA (n=167). The general disease activity parameters, however, were comparable between the two groups. A similar analysis on those patients fulfilling the ASAS axial SpA criteria (n=223) confirmed a younger age at disease onset and an increased frequency of uveitis and positive family history in the HLA-B27 positive (n=170) versus negative (n=53) patients. However, sacroiliitis on X-ray was less prevalent in the HLA-B27 positive group (65.7 vs. 81.1%), reflecting the fact that HLA-B27 negative patients have to fulfil the imaging arm to classify as SpA according to the ASAS axial criteria while HLA-B27 positive patients may fulfil the clinical arm without having imaging abnormalities. Again the disease activity was comparable between the two groups. A similar analysis of ASAS peripheral SpA (n=66) indicated that IBP occurred less frequently (0.0 vs. 27.1%) and sacroiliitis more frequently (16.7 vs. 2.1%) in the HLA-B27 positive (n=18) versus negative (n=48) group. The paradoxical lower frequency of IBP in HLA-B27 positive peripheral SpA is again a direct effect of the criteria since HLA-B27 positive patients with active IBP should be classified as axial SpA rather than peripheral SpA, even if peripheral disease is clinically dominant. Also in peripheral SpA, there were no differences in disease activity between the two groups. Conclusions: HLA-B27 positive SpA presents at a younger age, has more axial and less peripheral disease, and has more frequently uveitis and a positive family history. Classification according to the ASAS criteria, however, leads to paradoxical skewing of disease characteristics, such as less sacroiliitis in HLA-B27 positive axial SpA. Disease activity is similar in HLA-B27 positive and negative patients, independently of classification. Disclosure of Interest: None Declared